2021
DOI: 10.1128/mbio.03514-20
|View full text |Cite
|
Sign up to set email alerts
|

HBV Core Protein Is in Flux between Cytoplasmic, Nuclear, and Nucleolar Compartments

Abstract: Hepatitis B virus (HBV) core protein (Cp) can be found in the nucleus and cytoplasm of infected hepatocytes; however, it preferentially segregates to a specific compartment correlating with disease status. Regulation of this intracellular partitioning of Cp remains obscure. In this paper, we report that cellular compartments are filled and vacated by Cp in a time- and concentration-dependent manner in both transfections and infections. At early times after transfection, Cp, in a dimeric state, preferentially l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…Each of these steps requires extensive and intricate interaction of viral components and host factors. The import of rcDNA from the cytoplasm into the nucleus likely involves a conformational change or the partial disassembly of capsid to display its NLS on the outside surface, which interacts with karyopherin α and β, and results in NPC localization of the nucleocapsid [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. POL has also been shown to contain a bipartite NLS that could be exposed by casein kinase II (CKII)-dependent phosphorylation and interact with karyopherin α2, contributing to the import of rcDNA into the nucleus [ 41 ].…”
Section: Overview Of Hbv Life Cycle and Cccdna Biogenesismentioning
confidence: 99%
“…Each of these steps requires extensive and intricate interaction of viral components and host factors. The import of rcDNA from the cytoplasm into the nucleus likely involves a conformational change or the partial disassembly of capsid to display its NLS on the outside surface, which interacts with karyopherin α and β, and results in NPC localization of the nucleocapsid [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. POL has also been shown to contain a bipartite NLS that could be exposed by casein kinase II (CKII)-dependent phosphorylation and interact with karyopherin α2, contributing to the import of rcDNA into the nucleus [ 41 ].…”
Section: Overview Of Hbv Life Cycle and Cccdna Biogenesismentioning
confidence: 99%
“…Notably, Cp also contains nuclear export signals (NESs) [ 33 ], making it a nucleocytoplasmic shuttling protein [ 34 ]. Beyond previous evidence a recent study found Cp to shuttle, upon translation in the cytoplasm, with time and dependent on Cp concentration and assembly status, to the nucleoli, then to the nucleoplasm and eventually back to the cytoplasm [ 35 ]; more work will be needed to sort out the functional correlates of these different, apparently regulated, intracellular localizations.…”
Section: Functional Dynamics Of the Hbv Core Protein And Capsid In Virus Replicationmentioning
confidence: 99%
“…The subcellular localization of the Cp is rather complex, depending on both the intrinsic factors (NLS and NES) and the extrinsic factors (importins, Nxf1, and cellular kinase) [220]. A recent study showed that increasing the nuclear Cp concentration induces Cp export in a Crm1-dependent manner, which suggests that the Cp concentration may manipulate different export signals [221]. An empty Cp can interact with importin-β1 independent of importin-α via its IBB domain, but the exact biological function of this interaction is yet to be elucidated [222].…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%